The relation of body fats, anthropometric factor and physiological functions of Iranian female national judo team - Nazar Ali, P.; Hanachi, P.; Rezaei Nejad, N. (Modern Applied Science, 2010)
Both the IJF (International Judo Federation) and the IOC (International Olympic Committee) regulations require athletes to compete in set weight categories. Competitors are matched by weight divisions, thus players demonstrate relatively low levels of body fat with a high strength to mass ratio, and therefore the purpose of this study was to investigate the relation of body fats, anthropometric factors and physiological functions of Iranian female national judo players. The participants of this study were eight players of Iranian Judo national team (age, 22.5± 2.4yr; weight, 66.01± 6.4kg; height, 165± 6.6cm). The physiological profile was composed of aerobic (maximal test) and anaerobic power (ergo amp test). For anthropometric and body composition profiles, height, weights, body fat percentage, body mass index (BMI), waist hip ratio (WHR) were measured. Correlations were found between weight and body fat percentage and WHR. However negative correlation was found between aerobic and anaerobic power. Also positive correlation was found between BMI and lean body mass. Finding has showed judo players in this study, were almost favorite in terms of aerobics power and weight. The judo players who presenting higher aerobic power present a better performance in high-intensity intermittent activities; judo players with larger circumferences present higher absolute maximal strength, but this relation was not significant when strength was expressed relative to body weight. While these variables do not necessarily predict performance in a sport where technique and tactics are essential elements for success, they may provide some goals for developing judo players.